Radio/X-ray monitoring of the broad-line radio galaxy 3C 382. High-energy view with XMM–Newton and NuSTAR. Issue 2 (15th May 2018) - Ursini, F; Petrucci, P-O; Matt, G; Bianchi, S; Cappi, M; Dadina, M; Grandi, P; Torresi, E; Ballantyne, D R; De Marco, B; De Rosa, A; Giroletti, M; et al.
ABSTRACT: We present the analysis of five joint XMM–Newton / NuSTAR observations, 20 ks each and separated by 12 days, of the broad-line radio galaxy 3C 382. The data were obtained as part of a campaign performed in September–October 2016 simultaneously with Very Long Baseline Array . The radio data and their relation with the X-ray ones will be discussed in a following paper. The source exhibits a moderate flux variability in the UV/X-ray bands, and a limited spectral variability especially in the soft X-ray band. In agreement with past observations, we find the presence of a warm absorber, an iron Kα line with no associated Compton reflection hump, and a variable soft excess well described by a thermal Comptonization component. The data are consistent with a 'two-corona' scenario, in which the UV emission and soft excess are produced by a warm ( kT ≃ 0.6 keV), optically thick (τ ≃ 20) corona consistent with being a slab fully covering a nearly passive accretion disc, while the hard X-ray emission is due to a hot corona intercepting roughly 10 per cent of the soft emission. These results are remarkably similar to those generally found in radio-quiet Seyferts, thus suggesting a common accretion mechanism.